2015
DOI: 10.1007/s10067-015-2955-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum resistin levels in patients with rheumatoid arthritis and systemic lupus erythematosus: a meta-analysis

Abstract: The purpose of this meta-analysis was to investigate whether serum resistin level was associated with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) by comparing serum resistin levels between RA or SLE patients and normal controls. PubMed and EMBASE databases (up to May 13, 2014) were used to search all related articles. The weighted mean differences (WMDs) with 95 % confidence interval (CI) were calculated using random-effect model analysis. The Cochrane Q test and I(2) statistic were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 37 publications
1
35
1
1
Order By: Relevance
“…Recently, Bustos Rivera-Bahena et al (2015) [24] demonstrated that resistin levels correlated positively with clinical manifestations of disease activity in patients with RA, albeit of patient body mass index. Huang et al (2015) [38] in a meta-analysis concluded that serum resistin levels were significantly higher in RA patients compared to control group. However, some authors did not show significant associations between serum resistin and HOMA-IR, nor differences between serum and synovial fluid resistin levels between RA patients and controls [19].…”
Section: Resistinmentioning
confidence: 99%
“…Recently, Bustos Rivera-Bahena et al (2015) [24] demonstrated that resistin levels correlated positively with clinical manifestations of disease activity in patients with RA, albeit of patient body mass index. Huang et al (2015) [38] in a meta-analysis concluded that serum resistin levels were significantly higher in RA patients compared to control group. However, some authors did not show significant associations between serum resistin and HOMA-IR, nor differences between serum and synovial fluid resistin levels between RA patients and controls [19].…”
Section: Resistinmentioning
confidence: 99%
“…We identified several genes that were differentially expressed in patients with flare activity, including the RETN gene, encoding the proinflammatory adipokine resistin (Figure c). Interestingly, serum resistin levels were elevated in patients with rheumatoid arthritis and/or SLE, although the differences were reported not significant in unstratified patients with SLE, where high heterogeneity was noted . The specificity of elevated resistin levels to flare‐active patients may explain these results.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, serum resistin levels were elevated in patients with rheumatoid arthritis and/or SLE, although the differences were reported not significant in unstratified patients with SLE, where high heterogeneity was noted. 44 The specificity of elevated resistin levels to flareactive patients may explain these results. However, longitudinal studies monitoring successive flares are needed to validate these observations, to identify new flare-predicting transcriptional signatures and to harness this information for better management of patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, results from these studies were inconsistent, and several studies had suggested that no significant difference was found in the serum expression level of resistin between RA patients and healthy controls . To further analyze serum resistin level in RA patients, a comprehensive meta‐analysis was performed and the result indicated that serum resistin level in RA patients was significantly elevated . In addition, the serum resistin levels were related to clinical disease activity, CRP and ESR in RA .…”
Section: Discussionmentioning
confidence: 99%